Analisis peran guru dalam memotivasi belajar peserta didik kelas iv sekolah dasar - Ermas Brian Andana; Sri Marmoah; Sularmi Sularmi (Universitas Sebelas Maret, 2022)
In education, efforts are made to improve the quality of teaching and learning materials and methods. In this case, the teacher's effort to be able to increase the effectiveness and quality of learning is by making various plans for learning activities in the classroom. Thus it is necessary that the role of the teacher can increase student motivation and increase student learning output which also personally increases teacher performance. The purpose of this study was to knowing the teacher's role in motivating the fourth grade of elementary school students' learning. This research was conducted in class IV elementary school. The research method used is descriptive qualitative with a case study approach. The data were collected by means of interviews, observations, and questionnaires from teachers and students. The results showed that it can be concluded that many students have been motivated to learn because the teacher has carried out several activities that indirectly increase motivation in learning.. The role of the teacher in increasing the learning motivation of fourth grade elementary school students has been carried out by the teacher well by increasing the performance as a teacher of course also with student initiative, of course it can also increase student learning motivation.